Factor price equalization under joint production: A general equilibrium synthesis - Max Albert; Wilhelm K. Kohler (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1995)
We investigate how joint production affects the likelihood of factor price equalization (FPE) through trade. Following up on recent contributions by Samuelson (1992) and Jones (1992), we propose to take the relative size of the FPE region of endowment distributions to measure this likelihood. We show that the likelihood (1) may increase even if joint production leads to a decrease of the number of basic production processes, and (2) may decrease even if the number of basic production processes operated in equilibrium is the same as under non-joint production. Moreover, we reinterpret the formal arguments and apply them to a comparison between trade in intermediate versus trade in finished products. Our analysis throws light on the basic mechanism at work. It shows that goods trade and factor movements can be complements: Further integration of product markets can destroy FPE and create factor-price differences, thereby generating factor movements.
Keywords: 330